High-refractive-index resin hardening liquid and preparation method thereof
By using high-refractive metal oxide sol and cyclic sulfur monomer hardening liquid on the surface of the resin lens, the problem of insufficient adhesion and wear resistance in the prior art is solved, and high hardness, wear resistance and high permeability are achieved The effect of lightness.
Patent Information
- Application Number
- CN202411399947.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-10
AI Technical Summary
The existing high refractive index hardening fluids are difficult to form strong adhesion, good film formation, high light transmittance and appropriate solvent volatility on the surface of the resin, and it is difficult to meet the friction resistance requirements of the lens.
Use resin hardening liquid containing high refractive index metal oxide sol and cyclic sulfur monomer to improve the toughness of the hardening layer and the adhesion of the film layer through coupling reaction, adjust the composition to match the refractive index of the resin material, and form a solid film. and improve the wear resistance of the lens.
The high hardness and wear resistance of the surface of the high-refractive index resin lens are achieved, the interfacial light scattering is avoided, the visible light transmittance is improved, and the strong adhesion between the coating layer and the substrate is ensured, and the film layer is removed from the film layer.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to a resin lens surface hardening liquid, in particular to a resin hardening liquid containing a high-refractive-index metal oxide sol and an episulfide compound. Background Art
[0002] According to the refractive index, optical resins can be divided into low refractive index (n d <1.56), medium refractive index (1.56≤n d ≤1.61), high refractive index (1.61<n d ≤1.74), and ultra-high refractive index n d >1.74 and other different varieties of resins. The disadvantage of optical resin materials is that their surface strength is not high. Lens substrates made of various resins are prone to scratches and abrasions and cannot be used directly. High refractive index hardening liquid is a material mainly used to harden the surface of optical resin lenses with high refractive index. Its main technical feature is that it can form a hardened layer on the surface of the resin, thereby increasing the surface hardness of the resin, making the lens more scratch-resistant and durable. High refractive index hardening liquid is widely used in optical components such as lenses and lenses to increase the surface hardness of lenses and lenses, reduce scratches, and increase wear resistance, effectively resisting wear and tear in daily use. The technical background of high refractive index hardening liquid for lenses involves the comprehensive progress of materials science and processing technology. It not only improves the optical performance and durability of lenses, but also makes glasses more beautiful, lightweight and comfortable.
[0003] The method of using lens hardening liquid is usually to immerse the base sheet of the resin lens in it and slowly pull it into a film. After a curing process, a hard coating is formed on the surface of the lens to increase the surface hardness of the resin lens, thereby greatly improving the friction resistance of the resin lens. This process is called hardening.
[0004] The coating after curing by the hardening liquid must have a similar refractive index to the resin substrate it protects, otherwise it is easy to cause refraction and scattering of light between the resin substrate and the hardening layer interface, thereby reducing the light transmittance of the lens, reducing the clarity of the lens imaging, or causing inaccurate light. Therefore, the components and refractive index of the hardening liquid used for different refractive indices or different material resin lens substrates are different. Within a certain refractive index range, the refractive index can be appropriately adjusted by adjusting the components and content of the hardening liquid without affecting the comprehensive performance of the hard coating layer.
[0005] After the hardening liquid is formed into a film, it must produce strong adhesion on the surface of the substrate material to form a solid film. At the same time, it serves as a base to connect the subsequent coating layer, so that light can pass through the lens smoothly without refraction and scattering, and ensure that the coating layer will not peel off from the lens surface under external forces, temperature changes and other conditions.
[0006] Inorganic nanoparticles such as titanium dioxide, zirconium oxide, and zinc oxide are often used to produce high-refractive index hardening liquids because of their high refractive index and hardness. For example, mixing inorganic nanoparticles with functional monomers and additives can obtain a high-refractive index hardening liquid for lenses (a high-refractive index resin hardening liquid and its preparation method, CN202010520823.2). In the hardening liquid, the morphology of the high-refractive component is diverse, and its main function is to provide a higher refractive index and surface hardness. However, it is difficult to meet the performance requirements of the hardening liquid on the resin surface, such as strong adhesion, good film-forming properties, high light transmittance, good leveling properties, and appropriate solvent evaporation rate, by relying solely on the high-refractive component. These properties all require other components with specific functions to be combined with the high-refractive component into a reasonable formula to achieve. Although various commercial hardening liquids are currently on sale in the market, it is still necessary to improve the mechanical, processing and other properties of the hardening liquid. Summary of the invention
[0007] In view of the above problems in the prior art, the present invention provides a high refractive index resin hardening liquid and a preparation method thereof. The resin hardening liquid contains a metal oxide sol with a high refractive index and high wear resistance, and improves the toughness and film adhesion of the hardened layer by coupling with a high refractive index cyclosulfide monomer. The hardening liquid can enhance the surface hardness of the resin lens, improve the film firmness between the coating layer and the substrate, and enhance the friction resistance of the lens.
[0008] To achieve the above object, the present invention adopts the following technical solutions:
[0009] A high refractive index resin hardening liquid, comprising 20-60 parts by weight of a high refractive index sol, 10-30 parts by weight of an episulfide monomer, 10-30 parts by weight of a coupling agent, 1-5 parts by weight of aluminum acetylacetonate, and 10-50 parts by weight of an alcohol and / or ether solvent;
[0010] The high-fold sol is a sol containing titanium dioxide, zirconium oxide and / or aluminum oxide prepared by a sol-gel method, and the concentration of the metal oxide in the high-fold sol is 10-100wt%;
[0011] The general formula of the episulfide monomer is:
[0012]
[0013] Wherein, n=1, 2 or 3; R is a C1-3 alkyl group or an aromatic hydrocarbon group containing 1 to 2 benzene rings;
[0014] or
[0015]
[0016] Wherein, n=1, 2 or 3; R is a C1-3 alkyl group or an aromatic hydrocarbon group containing 1 to 2 benzene rings.
[0017] The high refractive index resin hardening liquid as described above, preferably, the hardening liquid contains 30N50 parts by mass of high refractive index sol, 15-25 parts by mass of episulfide monomer, 15-25 parts by mass of coupling agent, 2-4 parts by mass of aluminum acetylacetonate and 20-40 parts by mass of alcohol and / or ether solvent;
[0018] The high-fold sol is a sol containing titanium dioxide, zirconium oxide and / or aluminum oxide prepared by a sol-gel method. The concentration of the metal oxide in the high-fold sol is 10-40wt%.
[0019] In the high refractive index resin hardening liquid as described above, preferably, the coupling agent is at least one of a silane coupling agent, a titanate coupling agent, a zirconate coupling agent and an aluminate coupling agent.
[0020] As described above, in the high refractive index resin hardening liquid, preferably, the silane coupling agent is selected from at least one of kh550, kh540, kh560, kh570, kh792, kh602, DL602, DL171 or 3-isocyanate triethoxysilane.
[0021] As described above, the high refractive index resin hardening liquid, preferably, the titanate coupling agent is selected from at least one of isopropyl triisostearate titanate, isopropyl triisostearate titanate compound, isopropyl dioleyl (dioctyl phosphate) titanate, isopropyl tri(dioctyl phosphate) titanate, isopropyl trioleyl titanate, bis(dioctyl pyrophosphate) ethylene titanate, a chelate of bis(dioctyl pyrophosphate) ethylene titanate and triethanolamine, and tetraisopropyl di(dioctyl phosphite) titanate.
[0022] As described above, in the high refractive index resin hardening liquid, preferably, the aluminate coupling agent is selected from at least one of distearoyloxyisopropyl aluminate, DL-411, DL-411AF, DL-411D, DL-411DF, anti-settling aluminate ASA, isopropoxy distearoyloxy aluminate, liquid aluminate coupling agent PN-827 and triisopropoxy aluminum.
[0023] As described above, in the high refractive index resin hardening liquid, preferably, the zirconate coupling agent is selected from at least one of tetrakis(triethanolamine)zirconate, bis(diethyl citrate)dipropoxyzirconium chelate, sodium zirconium lactate, alkoxytri(vinyl-ethoxy)zirconate or alkoxytri(p-aminophenoxy)zirconate.
[0024] In the high refractive index resin hardening liquid as described above, preferably, the alcohol solvent is selected from at least one of methanol, ethanol, propanol, butanol, isopropanol, ethylene glycol, glycerol, isobutanol, butanediol, isoprene glycol and pentaerythritol, and the ether solvent is ethylene glycol ethyl ether or ethylene glycol butyl ether.
[0025] The high refractive index resin hardening solution as described above, preferably, the high refractive index sol is prepared by the following method:
[0026] (1) dissolving an acid source in a solvent to prepare an acidic solution having a pH value less than 3, wherein the acid source is at least one of hydrochloric acid, nitric acid, sulfuric acid, acetic acid and benzenesulfonic acid; and the solvent is at least one of water, methanol, ethanol, propanol, isopropanol and dimethylformamide;
[0027] (2) taking 20-70 parts by weight of an acidic solution, adding 30-80 parts by weight of at least one of tetrabutyl titanate, titanium tetrachloride, titanium sulfate, aluminum nitrate, aluminum chloride, aluminum hydroxide, zirconium nitrate, zirconium chloride and zirconium hydroxide;
[0028] (3) Stir the above solution until it is uniform to obtain a high-fold sol.
[0029] On the other hand, the present invention provides a method for preparing the high refractive index resin hardening solution as described above, the method comprising the following steps:
[0030] I. adding the episulfide monomer to the high-fold sol and stirring evenly;
[0031] II. The coupling agent and aluminum acetylacetonate are added to the solution obtained in step I and stirred evenly;
[0032] III. Add the solvent to the mixed solution obtained in step II and stir evenly to obtain a high refractive index resin hardening solution.
[0033] The beneficial effects of the present invention are as follows:
[0034] (1) The hardening liquid of the present invention has a very high refractive index and can be used to harden the surface of a resin material having a refractive index of 1.68-1.81, thereby increasing the surface hardness and wear resistance of the resin material.
[0035] (2) By adjusting the composition of the hardening liquid of the present invention, the refractive index of the surface coating formed by the hardening liquid can be adjusted to match the resin material with a refractive index of 1.68-1.81, thereby avoiding interface light scattering and obtaining a higher visible light transmittance.
[0036] (3) The coating formed by the hardening liquid of the present invention can produce strong adhesion with high-refractive-index optical resin materials and coating materials such as silicon dioxide and zirconium dioxide, and film peeling is not likely to occur. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a scanning electron microscope photograph of the surface and cross-section of a polyurethane lens having a refractive index of 1.74 after hard coating with the hardening liquid in Example 9. DETAILED DESCRIPTION
[0038] The present invention will be described in more detail below based on examples and test examples, but the present invention is not limited thereto.
[0039] Embodiment 1:
[0040] 1. Prepare a hardening liquid with a refractive index of 1.68
[0041] (1) 1 ml of 10 mol / L hydrochloric acid is dissolved in 100 L of a mixed solvent of water, methanol and isopropanol to prepare an acidic solution, wherein the mass ratio of water, methanol and isopropanol is 1:39:60.
[0042] (2) Take 70 parts by mass of the acidic solution and add 30 parts by mass of titanium tetrachloride.
[0043] (3) Stir the above solution until it is uniform to obtain a high-fold sol.
[0044] (4) 30 parts by weight of an episulfide monomer having the structural formula shown below is added to 20 parts by weight of the high-fold sol and stirred until it is uniformly dissolved.
[0045] The molecular structure of episulfide monomer is:
[0046]
[0047] n=1, and R is a methylene group.
[0048] (5) Add 10 parts by mass of KH560 and 5 parts by mass of aluminum acetylacetonate to the sol in step (4), and stir until completely dissolved.
[0049] (6) 20 parts by weight of ethylene glycol ethyl ether and 15 parts by weight of methanol were added to the sol in step (5) and stirred uniformly to obtain a 1.68 g hardening liquid product.
[0050] 2.1.68 Hard coating process with hardening liquid
[0051] (1) Using the hardening liquid prepared in step 1, hardening a polyurethane lens having a refractive index of 1.68, the specific operation is as follows:
[0052] i. Cool and dry the lens in the hard cooling zone for 144 seconds at a cooling temperature of 18°C.
[0053] ii. The cooled lens is dip-coated in a hardening tank at a temperature of 13°C;
[0054] iii. Drying in three drying chambers in sequence, with temperatures of 70°C, 70°C, and 68°C, respectively, and a drying time of 432 seconds;
[0055] iv. Place the dried lens in an oven and cure it at 105°C for 2 hours to obtain a 4-micron-thick hardened layer.
[0056] (2) Hardened lens coating
[0057] The hardened lens obtained in step 1 is coated with a vacuum coating machine. The order of coating materials and process conditions are shown in Table 1, and a finished lens with a coating thickness of 400 nanometers is obtained.
[0058] Table 1
[0059] Material <![CDATA[sio 2 ]]> <![CDATA[zro 2 ]]> <![CDATA[sio 2 ]]> <![CDATA[zro 2 ]]> ITO <![CDATA[sio 2 ]]> HT-100 Rate (nm / s) 18 5 8 5 1.5 12 2
[0060] 3. Lens performance testing
[0061] (1) The refractive index of the substrate is 1.68 and the transmittance is 88%. After the hardening step, the refractive index of the lens is 1.68 and the transmittance is 88%. After coating, the transmittance of the finished product increases to 91%.
[0062] (2) Friction test experiment to test the friction resistance of the film layer
[0063] Place the finished lens flat on the platform of the friction tester, put a steel wool on the A side of the lens, set the load of the steel wool to 1 kg, and set the friction time to 10 minutes. After the test, observe the surface with the naked eye. If there are visible scratches, it is unqualified.
[0064] (3) Boiling water resistance test
[0065] Take at least 5 finished lenses and boil them in 100 degrees Celsius boiling water for 15 minutes, and observe with the naked eye whether the film layer is cracked.
[0066] Inspection items Standard Terms Test results Refractive Index QB / T2506 1.681 Friction resistance GB0810.5-2012 qualified Boiling water resistance - qualified
[0067] Embodiment 2:
[0068] 1. Prepare a hardening liquid with a refractive index of 1.68
[0069] (1) 1 liter of acetic acid is dissolved in 100 liters of a mixed solvent of water, methanol and isopropanol to prepare an acidic solution, wherein the mass ratio of water, methanol and isopropanol is 5:35:60.
[0070] (2) Take 30 parts by mass of the acid solution, add 30 parts by mass of tetrabutyl titanate and 10 parts by mass of zirconium nitrate.
[0071] (3) Stir the above solution until it is uniform to obtain a high-fold sol.
[0072] (4) 30 parts by weight of an episulfide monomer having the structural formula shown below is added to 20 parts by weight of the high-fold sol and stirred until it is uniformly dissolved.
[0073] The molecular structure of episulfide monomer is:
[0074]
[0075] n=1,R is CH 2 CH 2 .
[0076] (5) Add 10 parts by mass of KH560 and 5 parts by mass of aluminum acetylacetonate to the sol in step (4), and stir until completely dissolved.
[0077] (6) 20 parts by weight of ethylene glycol ethyl ether and 15 parts by weight of methanol were added to the sol in step (5) and stirred uniformly to obtain a 1.68 g hardening liquid product.
[0078] 2.1.68 Hard coating process with hardening liquid
[0079] The hard coating process is the same as that in Example 1.
[0080] 3. Lens performance testing
[0081] The refractive index of the substrate is 1.68 and the light transmittance is 88%. After the hardening step, the refractive index of the lens is 1.68 and the light transmittance is 88%. After coating, the light transmittance of the finished product increases to 90%.
[0082] The test methods for friction resistance and water boiling resistance are the same as those in Example 1.
[0083] Inspection items Standard Terms Test results Refractive Index QB / T2506 1.679 Friction resistance GB0810.5-2012 qualified Boiling water resistance - qualified
[0084] Embodiment 3:
[0085] 1. Prepare a hardening liquid with a refractive index of 1.68
[0086] (1) 1 ml of 10 mol / L nitric acid was dissolved in 100 L of a mixed solvent of water, methanol and isopropanol to prepare an acidic solution, wherein the mass ratio of water, methanol and isopropanol was 5:35:60.
[0087] (2) Take 20 parts by mass of the acid solution, add 20 parts by mass of tetrabutyl titanate and 10 parts by mass of titanium tetrachloride.
[0088] (3) Stir the above solution until it is uniform to obtain a high-fold sol.
[0089] (4) 30 parts by weight of an episulfide monomer having the structural formula shown below is added to 20 parts by weight of the high-fold sol and stirred until it is uniformly dissolved.
[0090] The molecular structure of episulfide monomer is:
[0091]
[0092] n=2,R is CH 2 CH 2 CH.
[0093] (5) Add 15 parts by mass of KH570 and 5 parts by mass of aluminum acetylacetonate to the sol in step (4), and stir until completely dissolved.
[0094] (6) 10 parts by mass of ethylene glycol butyl ether, 10 parts by mass of isopropanol and 15 parts by mass of methanol were added to the sol in step (5) and stirred uniformly to obtain a 1.68 hardening liquid product.
[0095] 2.1.68 Hard coating process with hardening liquid
[0096] The hard coating process is the same as that in Example 1.
[0097] 3. Lens performance testing
[0098] The refractive index of the substrate is 1.68 and the light transmittance is 88%. After the hardening step, the refractive index of the lens is 1.68 and the light transmittance is 88%. After coating, the light transmittance of the finished product increases to 92%.
[0099] The test methods for friction resistance and water boiling resistance are the same as those in Example 1.
[0100] Inspection items Standard Terms Test results Refractive Index QB / T2506 1.681 Friction resistance GB0810.5-2012 qualified Boiling water resistance - qualified
[0101] Embodiment 4:
[0102] 1. Prepare a hardening liquid with a refractive index of 1.71
[0103] (1) 1 ml of 10 mol / L nitric acid was dissolved in 100 L of a mixed solvent of water, methanol and isopropanol to prepare an acidic solution, wherein the mass ratio of water, methanol and isopropanol was 5:35:60.
[0104] (2) Take 70 parts by mass of the acidic solution and add 50 parts by mass of titanium tetrachloride.
[0105] (3) Stir the above solution until it is uniform to obtain a high-fold sol.
[0106] (4) 25 parts by weight of an episulfide monomer having the structural formula shown below was added to 30 parts by weight of the high-fold sol and stirred until the mixture was uniformly dissolved.
[0107] The molecular structure of episulfide monomer is:
[0108]
[0109] n=1, and R is a methylene group.
[0110] (5) Add 10 parts by mass of KH560 and 5 parts by mass of aluminum acetylacetonate to the sol in step (4), and stir until completely dissolved.
[0111] (6) 10 parts by mass of ethylene glycol butyl ether, 10 parts by mass of isopropanol and 15 parts by mass of methanol were added to the sol in step (5) and stirred uniformly to obtain 1.71 hardening liquid product.
[0112] 2.1.71 Hard coating process with hardening liquid
[0113] The hard coating process is the same as that in Example 1.
[0114] 3. Lens performance testing
[0115] The refractive index of the substrate is 1.71 and the light transmittance is 89%. After the hardening step, the refractive index of the lens is 1.71 and the light transmittance is 89%. After coating, the light transmittance of the finished product increases to 91%.
[0116] The test methods for friction resistance and water boiling resistance are the same as those in Example 1.
[0117] Inspection items Standard Terms Test results Refractive Index QB / T2506 1.710 Friction resistance GB0810.5-2012 qualified Boiling water resistance - qualified
[0118] Embodiment 5:
[0119] 1. Prepare a hardening liquid with a refractive index of 1.71
[0120] (1) 1 liter of acetic acid is dissolved in 100 liters of a mixed solvent of water, methanol and isopropanol to prepare an acidic solution, wherein the mass ratio of water, methanol and isopropanol is 5:35:60.
[0121] (2) Take 20 parts by mass of the acid solution and add 40 parts by mass of tetrabutyl titanate.
[0122] (3) Stir the above solution until it is uniform to obtain a high-fold sol.
[0123] (4) 20 parts by weight of an episulfide monomer having the structural formula shown below is added to 40 parts by weight of the high-fold sol and stirred until it is uniformly dissolved.
[0124] The molecular structure of episulfide monomer is:
[0125]
[0126] n=1,R is CH 2 CH 2 .
[0127] (5) Add 10 parts by mass of KH560 and 5 parts by mass of aluminum acetylacetonate to the sol in step (4), and stir until completely dissolved.
[0128] (6) 10 parts by mass of ethylene glycol butyl ether, 10 parts by mass of isopropanol and 15 parts by mass of methanol were added to the sol in step (5) and stirred uniformly to obtain 1.71 hardening liquid product.
[0129] 2.1.71 Hard coating process with hardening liquid
[0130] The hard coating process is the same as that in Example 1.
[0131] 3. Lens performance testing
[0132] The refractive index of the substrate is 1.71 and the light transmittance is 89%. After the hardening step, the refractive index of the lens is 1.71 and the light transmittance is 89%. After coating, the light transmittance of the finished product increases to 94%.
[0133] The test methods for friction resistance and water boiling resistance are the same as those in Example 1.
[0134] Inspection items Standard Terms Test results Refractive Index QB / T2506 1.711 Friction resistance GB0810.5-2012 qualified Boiling water resistance - qualified
[0135] Embodiment 6:
[0136] 1. Prepare a hardening liquid with a refractive index of 1.71
[0137] (1) 1 ml of 10 mol / L nitric acid was dissolved in 100 L of a mixed solvent of water, methanol and isopropanol to prepare an acidic solution, wherein the mass ratio of water, methanol and isopropanol was 5:35:60.
[0138] (2) Take 70 parts by mass of the acid solution, add 40 parts by mass of titanium tetrachloride and 20 parts by mass of titanium sulfate.
[0139] (3) Stir the above solution until it is uniform to obtain a high-fold sol.
[0140] (4) 25 parts by weight of an episulfide monomer having the structural formula shown below was added to 30 parts by weight of the high-fold sol and stirred until the mixture was uniformly dissolved.
[0141] The molecular structure of episulfide monomer is:
[0142]
[0143] n=2, R is CH.
[0144] (5) Add 10 parts by mass of KH560 and 5 parts by mass of aluminum acetylacetonate to the sol in step (4), and stir until completely dissolved.
[0145] (6) 10 parts by mass of ethylene glycol butyl ether, 10 parts by mass of isopropanol and 15 parts by mass of methanol were added to the sol in step (5) and stirred uniformly to obtain 1.71 hardening liquid product.
[0146] 2.1.71 Hard coating process with hardening liquid
[0147] The hard coating process is the same as that in Example 1.
[0148] 3. Lens performance testing
[0149] The refractive index of the substrate is 1.71 and the light transmittance is 89%. After the hardening step, the refractive index of the lens is 1.71 and the light transmittance is 89%. After coating, the light transmittance of the finished product increases to 93%.
[0150] The test methods for friction resistance and water boiling resistance are the same as those in Example 1.
[0151] Inspection items Standard Terms Test results Refractive Index QB / T2506 1.711 Friction resistance GB0810.5-2012 qualified Boiling water resistance - qualified
[0152] Embodiment 7:
[0153] 1. Prepare a hardening liquid with a refractive index of 1.74
[0154] (1) 1 ml of 10 mol / L nitric acid was dissolved in 100 L of a mixed solvent of water, methanol and isopropanol to prepare an acidic solution, wherein the mass ratio of water, methanol and isopropanol was 5:35:60.
[0155] (2) Take 40 parts by mass of the acid solution, add 40 parts by mass of tetrabutyl titanate and 20 parts by mass of zirconium chloride.
[0156] (3) Stir the above solution until it is uniform to obtain a high-fold sol.
[0157] (4) 20 parts by weight of an episulfide monomer having the structural formula shown below is added to 30 parts by weight of the high-fold sol and stirred until it is uniformly dissolved.
[0158] The molecular structure of episulfide monomer is:
[0159]
[0160] n=2, R is CH.
[0161] (5) Add 10 parts by mass of KH560 and 5 parts by mass of aluminum acetylacetonate to the sol in step (4), and stir until completely dissolved.
[0162] (6) 10 parts by weight of ethylene glycol butyl ether, 15 parts by weight of isopropanol and 10 parts by weight of methanol were added to the sol in step (5) and stirred uniformly to obtain a 1.74 hardening liquid product.
[0163] 2.1.74 Hard coating process with hardening liquid
[0164] The hard coating process is the same as that in Example 1.
[0165] 3. Lens performance testing
[0166] The refractive index of the substrate is 1.74 and the light transmittance is 89%. After the hardening step, the refractive index of the lens is 1.74 and the light transmittance is 89%. After coating, the light transmittance of the finished product increases to 93%.
[0167] The test methods for friction resistance and water boiling resistance are the same as those in Example 1.
[0168] Inspection items Standard Terms Test results Refractive Index QB / T2506 1.740 Friction resistance GB0810.5-2012 qualified Boiling water resistance - qualified
[0169] Embodiment 8:
[0170] 1. Prepare a hardening liquid with a refractive index of 1.74
[0171] (1) 1 ml of 10 mol / L nitric acid was dissolved in 100 L of a mixed solvent of water, methanol and isopropanol to prepare an acidic solution, wherein the mass ratio of water, methanol and isopropanol was 5:35:60.
[0172] (2) Take 40 parts by mass of the acid solution, add 50 parts by mass of tetrabutyl titanate and 20 parts by mass of titanium sulfate.
[0173] (3) Stir the above solution until it is uniform to obtain a high-fold sol.
[0174] (4) 25 parts by weight of an episulfide monomer having the structural formula shown below was added to 30 parts by weight of the high-fold sol and stirred until the mixture was uniformly dissolved.
[0175] The molecular structure of episulfide monomer is:
[0176]
[0177] n=1, and R is a methylene group.
[0178] (5) Add 10 parts by mass of KH560 and 5 parts by mass of aluminum acetylacetonate to the sol in step (4), and stir until completely dissolved.
[0179] (6) 10 parts by weight of ethylene glycol butyl ether, 10 parts by weight of isopropanol and 10 parts by weight of methanol were added to the sol in step (5) and stirred uniformly to obtain a 1.74 hardening liquid product.
[0180] 2.1.74 Hard coating process with hardening liquid
[0181] The hard coating process is the same as that in Example 1.
[0182] 3. Lens performance testing
[0183] The refractive index of the substrate is 1.74 and the light transmittance is 89%. After the hardening step, the refractive index of the lens is 1.74 and the light transmittance is 89%. After coating, the light transmittance of the finished product increases to 93%.
[0184] The test methods for friction resistance and water boiling resistance are the same as those in Example 1.
[0185] Inspection items Standard Terms Test results Refractive Index QB / T2506 1.741 Friction resistance GB0810.5-2012 qualified Boiling water resistance - qualified
[0186] Embodiment 9:
[0187] 1. Prepare a hardening liquid with a refractive index of 1.74
[0188] 1. Prepare a hardening liquid with a refractive index of 1.74
[0189] (1) 1 ml of 10 mol / L nitric acid was dissolved in 100 L of a mixed solvent of water, methanol and isopropanol to prepare an acidic solution, wherein the mass ratio of water, methanol and isopropanol was 5:35:60.
[0190] (2) Take 40 parts by mass of the acid solution and add 50 parts by mass of tetrabutyl titanate.
[0191] (3) Stir the above solution until it is uniform to obtain a high-fold sol.
[0192] (4) 15 parts by weight of an episulfide monomer having the structural formula shown below was added to 35 parts by weight of the high-fold sol and stirred until the mixture was uniformly dissolved.
[0193] The molecular structure of episulfide monomer is:
[0194]
[0195] n=1, and R is a methylene group.
[0196] (5) Add 10 parts by mass of KH560 and 5 parts by mass of aluminum acetylacetonate to the sol in step (4), and stir until completely dissolved.
[0197] (6) 10 parts by weight of ethylene glycol butyl ether, 10 parts by weight of isopropanol and 10 parts by weight of methanol were added to the sol in step (5) and stirred uniformly to obtain a 1.74 hardening liquid product.
[0198] 2.1.74 Hard coating process with hardening liquid
[0199] The hardening liquid obtained in step (6) was used to form a hardening layer on the surface of the 1.74 lens by a dip coating method. After drying at 103 degrees for 2 hours, a coating layer was vacuum evaporated on the surface to obtain a finished lens. After the lens was quenched and broken, the cross section was sprayed with gold in a metal ion sputtering instrument to increase conductivity. The morphology was observed under an S-4800II field emission scanning electron microscope. Figure 1 As shown. Figure 1 The three-layer structure can be seen in the figure. The middle layer is the hardening layer, which is about 4 microns thick. The upper layer is the coating layer, which is about 500 nanometers thick. Figure 1 As can be seen from the left, the surface is smooth and flat after hard coating, which provides a guarantee for achieving high light transmittance. Figure 1 As can be seen on the right, the cross section of the hardened layer is smooth and crack-free, indicating that the components are very compatible. The hardened layer is tightly connected to the substrate and the coating layer without cracks, indicating that the layers are well bonded, ensuring the firmness of the film layer. There are slight diffusion marks between the hardened layer and the substrate, indicating that the hardened layer can penetrate into the surface of the substrate, providing adhesion to the film layer.
[0200] 3. Lens performance testing
[0201] The refractive index of the substrate is 1.74 and the light transmittance is 89%. After the hardening step, the refractive index of the lens is 1.74 and the light transmittance is 89%. After coating, the light transmittance of the finished product increases to 93%.
[0202] The test methods for friction resistance and water boiling resistance are the same as those in Example 1.
[0203] Inspection items Standard Terms Test results Refractive Index QB / T2506 1.740 Friction resistance GB0810.5-2012 qualified Boiling water resistance - qualified
[0204] Embodiment 10:
[0205] 1. Prepare a hardening liquid with a refractive index of 1.81
[0206] (1) 1 ml of 10 mol / L nitric acid was dissolved in 100 L of a mixed solvent of water, methanol and isopropanol to prepare an acidic solution, wherein the mass ratio of water, methanol and isopropanol was 5:35:60.
[0207] (2) Take 20 parts by mass of the acid solution and add 80 parts by mass of tetrabutyl titanate.
[0208] (3) Stir the above solution until it is uniform to obtain a high-fold sol.
[0209] (4) 30 parts by weight of an episulfide monomer having the structural formula shown below is added to 30 parts by weight of the high-fold sol and stirred until it is uniformly dissolved.
[0210] The molecular structure of episulfide monomer is:
[0211]
[0212] n=1, R is a benzene ring.
[0213] (5) Add 5 parts by mass of KH560 and 5 parts by mass of aluminum acetylacetonate to the sol in step (4) and stir until completely dissolved.
[0214] (6) 10 parts by mass of ethylene glycol ethyl ether, 10 parts by mass of isopropanol and 10 parts by mass of methanol were added to the sol in step (5) and stirred uniformly to obtain 1.81 hardening liquid product.
[0215] 2.1.81 Hard coating process with hardening liquid
[0216] The hard coating process is the same as that in Example 1.
[0217] 3. Lens performance testing
[0218] The refractive index of the substrate is 1.81 and the light transmittance is 89%. After the hardening step, the refractive index of the lens is 1.81 and the light transmittance is 89%. After coating, the light transmittance of the finished product increases to 93%.
[0219] The test methods for friction resistance and water boiling resistance are the same as those in Example 1.
[0220] Inspection items Standard Terms Test results Refractive Index QB / T2506 1.810 Friction resistance GB0810.5-2012 qualified Boiling water resistance - qualified
[0221] Embodiment 11:
[0222] 1. Prepare a hardening liquid with a refractive index of 1.81
[0223] (1) 1 ml of 10 mol / L hydrochloric acid is dissolved in 100 L of a mixed solvent of water, methanol and isopropanol to prepare an acidic solution, wherein the mass ratio of water, methanol and isopropanol is 5:35:60.
[0224] (2) Take 70 parts by mass of the acidic solution and add 80 parts by mass of titanium tetrachloride.
[0225] (3) Stir the above solution until it is uniform to obtain a high-fold sol.
[0226] (4) 10 parts by weight of an episulfide monomer having the structural formula shown below is added to 60 parts by weight of the high-fold sol and stirred until it is uniformly dissolved.
[0227] The molecular structure of episulfide monomer is:
[0228]
[0229] n=1, R is biphenyl.
[0230] (5) Add 5 parts by mass of KH560 and 5 parts by mass of aluminum acetylacetonate to the sol in step (4) and stir until completely dissolved.
[0231] (6) 10 parts by weight of ethylene glycol ethyl ether and 10 parts by weight of methanol were added to the sol in step (5) and stirred uniformly to obtain 1.81 of a hardened liquid product.
[0232] 2.1.81 Hard coating process with hardening liquid
[0233] The hard coating process is the same as that in Example 1.
[0234] 3. Lens performance testing
[0235] The refractive index of the substrate is 1.81 and the light transmittance is 89%. After the hardening step, the refractive index of the lens is 1.81 and the light transmittance is 89%. After coating, the light transmittance of the finished product increases to 93%.
[0236] The test methods for friction resistance and water boiling resistance are the same as those in Example 1.
[0237] Inspection items Standard Terms Test results Refractive Index QB / T2506 1.809 Friction resistance GB0810.5-2012 qualified Boiling water resistance - qualified
[0238] Embodiment 12:
[0239] 1. Prepare a hardening liquid with a refractive index of 1.81
[0240] (1) 0.5 liter of oxalic acid is dissolved in 100 liters of a mixed solvent of water, methanol and isopropanol to prepare an acidic solution, wherein the mass ratio of water, methanol and isopropanol is 5:35:60.
[0241] (2) Take 40 parts by mass of the acid solution, add 40 parts by mass of tetrabutyl titanate and 20 parts by mass of titanium tetrachloride.
[0242] (3) Stir the above solution until it is uniform to obtain a high-fold sol.
[0243] (4) 30 parts by weight of an episulfide monomer having the structural formula shown below is added to 30 parts by weight of the high-fold sol and stirred until it is uniformly dissolved.
[0244] The molecular structure of episulfide monomer is:
[0245]
[0246] n=1, R is a benzene ring.
[0247] (5) Add 5 parts by mass of KH560 and 5 parts by mass of aluminum acetylacetonate to the sol in step (4) and stir until completely dissolved.
[0248] (6) 10 parts by mass of ethylene glycol ethyl ether, 10 parts by mass of isopropanol and 10 parts by mass of methanol were added to the sol in step (5) and stirred uniformly to obtain 1.81 hardening liquid product.
[0249] 2.1.81 Hard coating process with hardening liquid
[0250] The hard coating process is the same as that in Example 1.
[0251] 3. Lens performance testing
[0252] The refractive index of the substrate is 1.81 and the light transmittance is 89%. After the hardening step, the refractive index of the lens is 1.81 and the light transmittance is 89%. After coating, the light transmittance of the finished product increases to 93%.
[0253] The test methods for friction resistance and water boiling resistance are the same as those in Example 1.
[0254] Inspection items Standard Terms Test results Refractive Index QB / T2506 1.809 Friction resistance GB0810.5-2012 qualified Boiling water resistance - qualified
[0255] Comparative Example 1
[0256] 1. Prepare a hardening liquid with a refractive index of 1.68
[0257] The hardening liquid was prepared in the same manner as in Example 1, but without adding the high-fold sol, to obtain Comparative Sample 1.
[0258] 2. Preparation of high refractive index and high hardness resin lenses
[0259] The lens is hardened and coated using the same method as in Example 1.
[0260] 3. Lens performance testing
[0261] The refractive index of the substrate is 1.68, and the light transmittance is 88%. The refractive index of the lens after the hardening step is 1.67, and the light transmittance is 88%. Compared with the lens hardened by the hardening liquid in Example 1, the refractive index decreases by 0.01; when rubbed by a steel ball with a load of 1 kg for 10 minutes, obvious scratches appear on the surface, indicating that the friction resistance is insufficient. After coating, the light transmittance of the finished product increases to 91%, and the refractive index of the finished product is 1.67, which is 0.01 lower than that of Example 1 and does not meet the refractive index requirements.
[0262] Comparative Example 2
[0263] 1. Prepare a hardening liquid with a refractive index of 1.71
[0264] A hardening solution was prepared in the same manner as in Example 4, but without adding the high-fold sol, to obtain a comparative sample.
[0265] 2. Preparation of high refractive index and high hardness resin lenses
[0266] The lens is hardened and coated using the same method as in Example 1.
[0267] 3. Lens performance testing
[0268] The refractive index of the substrate is 1.71, and the light transmittance is 89%. The refractive index of the lens after the hardening step is 1.69, and the light transmittance is 89%. Compared with the lens hardened by the hardening liquid in Example 1, the refractive index decreases by 0.02; when rubbed by a steel ball with a load of 1 kg for 10 minutes, obvious scratches appear on the surface, indicating that the friction resistance is insufficient. The light transmittance of the finished product after coating increases to 91%, and the refractive index of the finished product is 1.69, which is 0.02 lower than that of Example 1 and does not meet the refractive index requirements.
[0269] Comparative Example 3
[0270] 1. Prepare a hardening liquid with a refractive index of 1.74
[0271] A hardening solution was prepared in the same manner as in Example 7, but without adding the high-fold sol, to obtain a comparative sample.
[0272] 2. Preparation of high refractive index and high hardness resin lenses
[0273] The lens is hardened and coated using the same method as in Example 1.
[0274] 3. Lens performance testing
[0275] The refractive index of the substrate is 1.74, and the transmittance is 89%. The refractive index of the lens after the hardening step is 1.72, and the transmittance is 89%. Compared with the lens hardened by the hardening liquid in Example 1, the refractive index decreases by 0.02; when rubbed by a steel ball with a load of 1 kg for 10 minutes, obvious scratches appear on the surface, indicating that the friction resistance is insufficient. After coating, the transmittance of the finished product increases to 91%, and the refractive index of the finished product is 1.72, which is 0.02 lower than that of Example 1 and does not meet the refractive index requirements.
[0276] Comparative Example 4
[0277] 1. Prepare a hardening liquid with a refractive index of 1.81
[0278] A hardening solution was prepared in the same manner as in Example 10, but without adding the high-fold sol, to obtain a comparative sample.
[0279] 2. Preparation of high refractive index and high hardness resin lenses
[0280] The lens is hardened and coated using the same method as in Example 1.
[0281] 3. Lens performance testing
[0282] The refractive index of the substrate is 1.81, and the transmittance is 89%. The refractive index of the lens after the hardening step is 1.78, and the transmittance is 89%. Compared with the lens hardened by the hardening liquid in Example 1, the refractive index decreases by 0.03; when rubbed by a steel ball with a load of 1 kg for 10 minutes, obvious scratches appear on the surface, indicating that the friction resistance is insufficient. After coating, the transmittance of the finished product increases to 91%, and the refractive index of the finished product is 1.78, which is 0.03 lower than that of Example 1 and does not meet the refractive index requirements.
[0283] Comparative Example 5:
[0284] 1. Prepare a hardening liquid with a refractive index of 1.74
[0285] The hardening liquid was prepared in the same manner as in Example 7, but a nano-titanium dioxide colloidal solution with a particle size of 25 nanometers and a mass concentration of 20% was used instead of the high-fold sol to obtain a comparative sample.
[0286] 2. Preparation of high refractive index and high hardness resin lenses
[0287] The lens is hardened and coated using the same method as in Example 1.
[0288] 3. Lens performance testing
[0289] (1) The refractive index of the substrate is 1.74, and the light transmittance is 89%. The refractive index of the lens after the hardening step is 1.74, and the light transmittance is 89%, which is comparable to the lens hardened with the hardening liquid in Example 7.
[0290] (2) After coating, the transmittance of the finished product increases to 91%, and the refractive index of the finished product is 1.74, indicating that the transmittance is qualified.
[0291] (3) When rubbed with a steel wool with a load of 1 kg for 10 minutes, there are no obvious scratches on the surface, indicating that the friction resistance is qualified.
[0292] (4) After the lens has been boiled in water for 15 minutes, tiny cracks visible to the naked eye appear on the lens surface, which does not meet the requirements for water boiling resistance.
[0293] The boiling experiment shows that the hardening layer composed of metal oxide nanoparticles is more brittle and has lower adhesion to the lens than the hardening layer composed of the high refractive index sol in Example 7. This shows that adding high refractive index episulfide monomers to the hardening liquid composition can improve the mechanical properties of the hardening liquid.
[0294] Comparative Example 6:
[0295] 1. Prepare a hardening liquid with a refractive index of 1.81
[0296] The hardening liquid was prepared in the same manner as in Example 10, except that a nano-titanium dioxide colloidal solution with a particle size of 50 nanometers and a mass concentration of 20% was used instead of the high-fold sol to obtain a comparative sample.
[0297] 2. Preparation of high refractive index and high hardness resin lenses
[0298] The lens is hardened and coated using the same method as in Example 1.
[0299] 3. Lens performance testing
[0300] (1) The refractive index of the substrate is 1.81, and the light transmittance is 89%. The refractive index of the lens after the hardening step is 1.81, which is equivalent to the lens hardened with the hardening liquid in Example 10; the light transmittance is 88%, which is a decrease.
[0301] (2) The light transmittance of the finished product after coating increases to 90%, which is lower than the light transmittance of 93% in Example 10.
[0302] (3) When rubbed with a steel wool with a load of 1 kg for 10 minutes, there are no obvious scratches on the surface, indicating that the friction resistance is qualified.
[0303] (4) After being boiled in water for 15 minutes, tiny cracks visible to the naked eye appeared on the surface of the lens, which does not meet the requirements for water boiling resistance.
[0304] The reason for the performance degradation may be that when the refractive index of the hardening liquid is increased to 1.81, the amount of colloidal solution composed of titanium dioxide nanoparticles added is large, and the film layer appears to be agglomerated, causing light scattering and a decrease in light transmittance. At the same time, the hardening layer composed of metal oxide nanoparticles is more brittle than the hardening layer composed of high-refractive sol, and has lower adhesion to the lens, causing the film layer to crack when boiled in water.
Claims
1. A high refractive index resin hardening liquid, characterized in that: It contains 20-60 parts by mass of high-fold sol, 10-30 parts by mass of episulfide monomer, 10-30 parts by mass of coupling agent, 1-5 parts by mass of aluminum acetylacetonate and 10-50 parts by mass of alcohol and / or ether solvent; The high-fold sol is a sol containing titanium dioxide, zirconium oxide and / or aluminum oxide prepared by a sol-gel method, and the concentration of the metal oxide in the high-fold sol is 10-100wt%; The general formula of the episulfide monomer is: Wherein, n=1, 2 or 3; R is a C1-3 alkyl group or an aromatic hydrocarbon group containing 1 to 2 benzene rings; or Wherein, n=1, 2 or 3; R is a C1-3 alkyl group or an aromatic hydrocarbon group containing 1 to 2 benzene rings.
2. The high refractive index resin hardening liquid as claimed in claim 1, characterized in that: The hardening agent contains 30 to 50 parts by mass of high-fold sol, 15 to 25 parts by mass of episulfide monomer, 15 to 25 parts by mass of coupling agent, 2 to 4 parts by mass of aluminum acetylacetonate and 20 to 40 parts by mass of alcohol and / or ether solvent; The high-fold sol is a sol containing titanium dioxide, zirconium oxide and / or aluminum oxide prepared by a sol-gel method. The concentration of the metal oxide in the high-fold sol is 10-40wt%.
3. The high refractive index resin hardening liquid as claimed in claim 1, characterized in that: The coupling agent is at least one of a silane coupling agent, a titanate coupling agent, a zirconate coupling agent and an aluminate coupling agent.
4. The high refractive index resin hardening liquid as claimed in claim 1, characterized in that: The silane coupling agent is selected from at least one of kh550, kh540, kh560, kh570, kh792, kh602, DL602, DL171 and 3-isocyanate triethoxysilane.
5. The high refractive index resin hardening liquid as claimed in claim 1, characterized in that: The titanate coupling agent is selected from at least one of isopropyl triisostearate titanate, isopropyl triisostearate titanate compound, isopropyl dioleyl (dioctyl phosphate) titanate, isopropyl tri(dioctyl phosphate) titanate, isopropyl trioleyl titanate, bis(dioctyl pyrophosphate) ethylene titanate, a chelate of bis(dioctyl pyrophosphate) ethylene titanate and triethanolamine, and tetraisopropyl di(dioctyl phosphite) titanate.
6. The high refractive index resin hardening liquid as claimed in claim 1, characterized in that: The aluminate coupling agent is selected from at least one of distearoyloxyisopropyl aluminate, DL-411, DL-411AF, DL-411D, DL-411DF, anti-settling aluminate ASA, isopropoxy distearoyloxy aluminate, liquid aluminate coupling agent PN-827 and triisopropoxy aluminum.
7. The high refractive index resin hardening liquid as claimed in claim 1, characterized in that: The zirconate coupling agent is selected from at least one of tetrakis(triethanolamine)zirconate, bis(diethyl citrate)dipropoxy zirconium chelate, sodium zirconium lactate, alkoxy tris(vinyl-ethoxy)zirconate or alkoxy tris(p-aminophenoxy)zirconate.
8. The high refractive index resin hardening liquid as claimed in claim 1, characterized in that: The alcohol solvent is selected from at least one of methanol, ethanol, propanol, butanol, isopropanol, ethylene glycol, glycerol, isobutanol, butanediol, isopentyl glycol and pentaerythritol, and the ether solvent is ethylene glycol ethyl ether or ethylene glycol butyl ether.
9. The high refractive index resin hardening liquid according to any one of claims 1 to 8, characterized in that: The high-fold sol is prepared by the following method: (1) dissolving an acid source in a solvent to prepare an acidic solution having a pH value less than 3, wherein the acid source is at least one of hydrochloric acid, nitric acid, sulfuric acid, acetic acid and benzenesulfonic acid; and the solvent is at least one of water, methanol, ethanol, propanol, isopropanol and dimethylformamide; (2) taking 20-70 parts by weight of an acidic solution, adding 30-80 parts by weight of at least one of tetrabutyl titanate, titanium tetrachloride, titanium sulfate, aluminum nitrate, aluminum chloride, aluminum hydroxide, zirconium nitrate, zirconium chloride and zirconium hydroxide; (3) Stir the above solution until it is uniform to obtain a high-fold sol.
10. The method for preparing a high refractive index resin hardening liquid according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: I. adding the episulfide monomer to the high-fold sol and stirring evenly; II. The coupling agent and aluminum acetylacetonate are added to the solution obtained in step I and stirred evenly; III. Add the solvent to the mixed solution obtained in step II and stir evenly to obtain a high refractive index resin hardening solution.
Citation Information
Patent Citations
A high refractive index resin hardening liquid and its preparation method
CN111454659B
High-refractive-index resin hardening liquid and preparation method thereof
CN111454659A
High-refractive-index and high-hardness resin lens
CN111621048A
Medium-high refractive index resin hardening liquid and preparation method thereof
CN111675967A
Hardening method of high-refractive-index resin lens
CN111718512A